The susceptibility differences of buffalo and Ongole calves against trickle infection with Fasciola gigantica - Wiedosari, Ening; Widjajanti, S; Partoutomo, S (Indonesian Animal Sciences Society, 1998)
A pen trial was carried out in order to determine the susceptibility differences of a trickle infection with Fasciola gigantica in buffalo and Ongole calves. Treated animals were infected orally with 15 metacercariae of F. gigantica twice weekly for 32 weeks and were slaughtered at 36 weeks. The results showed that buffalo calves had significantly lower fluke burdens than Ongole calves (P<0 .01) . All of the infected Ongole calves had fasciola eggs in their faeces 18 weeks after the commencement of infection. In contrast, eggs were detected only in 3 out of 7 infected buffalo calves at week 20, in 4 at week 28 and in 6 at week 30. Faeces of the seventh buffalo remained free of eggs until week 36. Rates of growth were reduced by 25%and 10,3% in infected Ongole and buffalo calves respectively . Circulating blood eosinophilia ofboth hosts, ahallmark of helminth infections, increased following infection, but values in buffaloes was greater than Ongole calves mainly in week 4 and 8 after infection (P<0.01). These results might be concluded that the susceptibility of buffalo calves to trickle infection with F. gigantica was lower compared to Ongole calves. Â Keywords : Fasciola gigantica; susceptibility, buffalo calves, Ongole calves